2005
DOI: 10.1038/sj.onc.1208979
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of adult T-cell leukemia/lymphoma and approaches to therapy

Abstract: After cell-to-cell transmission, HTLV-I increases its viral genome by de novo infection and proliferation of infected cells. Proliferation of infected cells is clonal and persistent in vivo. During the carrier state, infected cells are selected in vivo by the host's immune system, the genetic and epigenetic environment of proviral integration sites, and other factors. In leukemic cells, tax gene expression is frequently impaired by genetic and epigenetic mechanisms. Such loss of Tax expression enables ATL cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
152
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(160 citation statements)
references
References 94 publications
2
152
0
6
Order By: Relevance
“…These observations suggest that the lower frequency and diversity of anti-Tax CD8 ϩ T cells is risk for ATL development. A recent report demonstrated insufficient expression of HTLV-1 Tax in vivo in ATL patients and suspected a role of Tax-specific CTL for therapy or prevention of ATL (48). However, other researchers, as well as our group, demonstrated clear expression of HTLV-1 Tax in short-term cultures of fresh ATL cells (24 -26).…”
Section: Discussionmentioning
confidence: 58%
“…These observations suggest that the lower frequency and diversity of anti-Tax CD8 ϩ T cells is risk for ATL development. A recent report demonstrated insufficient expression of HTLV-1 Tax in vivo in ATL patients and suspected a role of Tax-specific CTL for therapy or prevention of ATL (48). However, other researchers, as well as our group, demonstrated clear expression of HTLV-1 Tax in short-term cultures of fresh ATL cells (24 -26).…”
Section: Discussionmentioning
confidence: 58%
“…HBZ was found to inhibit Taxmediated transactivation of viral transcription from the 59LTR by interaction with cellular factors of the JUN and ATF/CREB families (Basbous et al, 2003;Lemasson et al, 2007). The HBZ transcript is reportedly detectable in all ATL cases without exception (Taylor& Matsuoka, 2005). Importantly, it has been reported that downregulation of HBZ results in inhibition of ATL cell growth, and that conversely, the expression of HBZ in human T-cell lines promotes their proliferation (Satou et al, 2006).…”
mentioning
confidence: 99%
“…Because Tax-specific cytotoxic T lymphocytes (CTLs) are frequently detected in peripheral blood of patients with ATL who have undergone allogeneic HSCT (Harashima et al, 2004), immunotherapy targeting Tax might be a promising strategy for treatment of ATL. However, universal clinical application of Tax-targeted immunotherapy seems unlikely because tax mRNA is detected in only about 40 % of ATL cases (Taylor& Matsuoka, 2005). Therefore, identification of a novel target antigen recognized by CTLs and directed against ATL cells is desirable.…”
mentioning
confidence: 99%
“…However, at present, there is no accepted curative therapy for ATL and the condition often progresses to death with a median survival time of 13 months in aggressive ATL. 4 Chemotherapies that are specifically known to be active against other lymphoid malignancies are ineffective for treating aggressive forms of ATL. Death is usually due to severe infection or hypercalcemia.…”
mentioning
confidence: 99%